Mathematical modeling of biohydrogen production via dark fermentation of fruit peel wastes by Clostridium butyricum NE95 - Norhan Elerakey; Abdel-Hamied M. Rasmey; Akram A. Aboseidah; Heba Hawary (BMC Biotechnology)
Abstract Background Biohydrogen production from agro-industrial wastes through dark fermentation offers several advantages including eco-friendliness, sustainability, and the simplicity of the process. This study aimed to produce biohydrogen from fruit and vegetable peel wastes (FVPWs) by anaerobic fermentative bacteria isolated from domestic wastewater. Kinetic analysis of the produced biohydrogen by five isolates on a glucose medium was analyzed using a modified Gompertz model (MGM). Besides, the feasibility of hydrogen production by Clostridium butyricum NE95 using FVPWs as substrates was investigated. Results The bacterial isolate NE95 was selected as the highest biohydrogen producer with maximum biohydrogen production (Hmax) of 1617.67 ± 3.84 mL/L, Rmax (MGM) of 870.77 mL/L/h and lag phase (λ) of 28.37 h. NE95 was phenotypically and genetically identified as C. butyricum and its 16 S rRNA gene sequence was deposited in the GenBank under the accession number PP581833. The genetic screening of hydrogenase gene clusters indicated the presence of Fe-Fe hydrogenase gene in C. butyricum NE95. C. butyricum NE95 showed the ability to produce biohydrogen from different FVPWs, with watermelon and melon peels being the most promising feedstocks for fermentation. It was revealed that using a mixture (1:1, w/w) of watermelon and melon peels as a substrate for C. butyricum NE95 significantly increased biohydrogen yield with Hmax of 991.00 ± 10.54 mL/L, Rmax of 236.31 mL/L/h, λ of 33.92 h and a high accuracy of R2 (0.997). Conclusions The study highlights the effectiveness of C. butyricum NE95 on the valorization of FVPWs and generates a sustainable source of biohydrogen production.